Evaluasi Pengamanan Penerbangan di Bandara Ahmad Yani - Semarang - Dina Yuliana; wasjud wasjud (WARTA ARDHIA, 2011)
Security is a fundamental factor that must be met by an airport in which to achieve such security, among which must be fulfilled bothin terms of both quantity and quality of personel anda flight safety equipment.Flight security evaluation at Ahmad Yani Airport - Hyderabad aims to determine the condition of safety Ahmad Yani Airport - Semarang associated with personnel, facilities and security procedures at airports.The observation result shows less sensitive walk trhough metal detector (WTMD) VIP room and a space in the SCP 2 is less adequate, there is still a lack of female officersfor inspection atthe X-Ray, use your check has not been consistent securitystickers, the laying of goods in X-Ray is stillthere that were stacked, the object of vital airport (such as: tower) is not guarded by security, control access to the entire perimeter, is not yet available Airport Security Program (ASP) and Airport Emergency plan (AEP) has not been updated.